Military aircraft visual encyclopedia (Amber Books, 2009)
The history of aviation is full of striking and unusual designs, from the biplanes and tri-planes of World War I, through the giant bombers and streamlined fighters of World War II and beyond, to the stealthy shapes and unusual configurations of modern military aircraft like the Northrop Grumman B-2 and V-22 Osprey. "Military Aircraft Visual Encyclopedia" provides a fascinating at-a-glance guide to every major military aircraft type ever flown, all illustrated with a detailed profile artwork, accompanied by brief details and specifications. Common types such as the Spitfire, Ju 87 Stuka, F-86 Sabre and F-4 Phantom are featured with several artworks showing the range of colour schemes and operators. Arranged chronologically by type to allow easy comparison, each featured aircraft or variant is illustrated with an excellent full-colour artwork, showing in great detail its characteristics and markings, and completed with an informative caption. Many aircraft are illustrated in profile, and others in a head-on view. With over 1000 outstanding colour artworks, "Military Aircraft Visual Encyclopedia" is an authoritatively researched book that celebrates the many diverse designs of more than a century of military aviation. It is a comprehensive, highly illustrated guide to military aircraft since 1914. It includes more than 1000 artworks that show each aircraft in profile in full colour accompanied by a detailed caption. It is an illustration-packed single-volume guide to military aviation.